EFEK PUPUK BOKASHI TERHADAP KETERSEDIAAN UNSUR BASA (K, Na, Ca, dan Mg) PADA INCEPTISOL KARANGPLOSO MALANG - Arumita Rohmah; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The Inceptisol of Karangploso Malang has low pH (5.33) and low C-organic content (1.39%). Efforts can be made to improve these problems through land management with the use of organic fertilizer. Bokashi is one of the composts produced from fermentation process with EM4 which can improve soil chemical properties, because bokashi has elements of N, P, K, Na, Ca, and Mg respectively 1.22%, 0.53%, 1.71%, 5.64%, 0.62% and 2.01%. This study was carried out at the Greenhouse and Chemical Laboratory of Soil Science Department, Agriculture Faculty, Brawijaya University. The design of this research was a completely randomized design with O0 treatment (control); O1 (Bokashi 5 t ha-1); O2 (Bokashi 10 t ha-1); O3 (Bokashi 15 t ha-1); O4 (Bokashi 20 t ha-1); O5 (Bokashi 25 t ha-1); O6 (Bokashi 30 t ha-1) which was repeated 3 times. Parameters measured were pH, CEC, BS, K-exch, Na-exch, Ca-exch, and Mg-exch on 1 MAI (month after incubation), and 2 MAI. The results showed thatÂ increasing the dose of bokashi application at 1 MAI significantly increased K-exch and Mg-exch compared to the control treatment, but did not significantly affect pH, CEC, BS, Na-exch, and Ca-exch. Furthermore, increasing the dose of bokashi application on 2 MAI significantly increased pH and K-exch compared to the control treatment, but did not significantly affect CEC, BS, Na-exch, Ca-exch, and Mg-exch.